SEJARAH SOSIAL PAKAIAN PENUTUP KEPALA MUSLIMAH DI SUMATERA BARAT - Lukman, Fadli (Musawa Jurnal Studi Gender dan Islam, 2014)
Wearing the veil relates very much to hermeneutical reception to the Qurâ€™an, though the development andÂ  variety of designs are in accordance with socio-cultural as well as political circumstances. This article discusses the existence of veil in West Sumatera, among the Minangkabau people after Paderi period. Applying a social-history approach with a descriptive-analitical method, this research ends with some interesting findings. In the past in West Sumatera, a specific veil called a mudawarah or lilik became popular as an effect of the reformation of Islamic Education there. The political policies of the New Order period, as well as during the reformation years of increased capitalism, the veil developed a new shape and the wearing of the mudawarah was slowly marginalized. This phenomena shows that although the aesthetic shape of the veil comes from initial text, its development shows such a creative interpretation of the text